Introducing the Concept of Autotheory in Literary Practices - Herceg, Emanuela (Anafora, 2025)
Autotheory is a new term in literary theory, which has gained popularity in literary and artistic circles within the English-speaking world in the first half of the twenty-first century. It is especially popular among feminist authors examining, through literary practices and art performances, personal experiences in relation to social concepts and theories (Lauren Fournier, Maggie Nelson, Paul B. Preciado). Autotheoretical writing denotes a philosophical examination of personal experiences by integrating autobiographical elements, memoirs, and critical theory to enable, through bodily experience, the formation of new theories and knowledge. Although the application of the concept of autotheory in literary practices is relatively recent, tendencies toward autoteorethical writing date back to ancient times (such as Plato’s writings about Socrates and Saint Augustine’s Confessions). This paper aims to introduce this concept, which has been relatively unknown in literary science, into literary theory to establish a methodology for researching literary practices, as well as for retroactively analyzing literary works that are traditionally considered to be autobiographical.